Perfusion index as a predictor of hypotension following induction of general anaesthesia with propofol-An observational study - Rithwik K Rajeev,; Aswathy S,; Vrinda M,; Yedudev SB, (Asian Journal of Medical Sciences, 2024)
Background: Perfusion index (PI) is a somewhat novel parameter evaluating the pulsatility of blood in the extremities, calculated using the infrared spectrum as a component of plethysmography waveform processing. Aims and Objectives: To obtain a cutoff value of pre-anesthesia PI, which may be helpful for the prediction of hypotension following anesthetic induction with propofol. Materials and Methods: This descriptive observational research was carried out at the Sree Gokulam medical college and research foundation, Venjaramoodu, Trivandrum, Kerala, from June 2020 to June 2021. A total of 174 patients of age group 17–60 years, with ASA 1 or 2 scheduled for surgery under general anesthesia, were included. The parameters (systolic blood pressure [SBP], diastolic blood pressure, mean arterial pressure, PI, and SPO2) were recorded until 5 min of induction. Intravenous (IV) fentanyl 2 μg/kg was administered, propofol injected was given slowly at a rate of 10 mg per every 5 s, titrated to loss of verbal communication responseuronium 0.1 mg/kg IV was administered. The calculation for hypertension was done 5 min after anesthesia. The predictive validity of PI was calculated, keeping SBP as the standard gold test. For statistical analysis coGuide software. Results: The cutoff value for PI at 5 min was low (≤2.45) for 27 (90%) participants and high (>2.45) for 3 (10%) participants. With a sensitivity of 90% in predicting hypotension and specificity of 87.50%, false-positive rate was 12.50%, false-negative rate was 10, positive predictive value was 60% (95 CI 44.43–74.30%), the negative predictive value (NPV) was 97.67%, and the total diagnostic accuracy was 87.93%. Conclusion: With the current study’s findings, we conclude that PI cutoff value 2.45 can be used to predict hypotension following anesthetic induction with propofol. It has a high NPV with fair diagnostic accuracy.